Multi-criteria decision-making for fisheries management: A case study of Mediterranean demersal fisheries. (March 2015) - Rossetto, Marisa; Bitetto, Isabella; Spedicato, Maria Teresa; Lembo, Giuseppe; Gambino, Monica; Accadia, Paolo; Melià, Paco
Abstract: A decision-making framework combining multi-attribute utility theory and the analytic hierarchy process is proposed to assess the performances of alternative fisheries management policies. The framework is demonstrated by applying it to a Mediterranean demersal fishery (GSA 18, Southern Adriatic Sea), for which a set of management scenarios are evaluated against their ability to cope with environmental, economic and social objectives. To this aim, (1) a suite of biological and socioeconomic indicators is identified and organized into an appropriate hierarchy; (2) a set of utility functions is defined to express the level of satisfaction associated with different values of the indicators; and (3) a set of weights, representing the relative importance of each indicator to the overall utility, is derived through a pair-wise comparison of the indicators. The proposed approach provides a practical decision-support tool to identify the management scenarios that are most desirable from the society׳s perspective, thus providing a good compromise between the environmental, economic and social aspects of the problem. The flexible structure of the framework allows the incorporation of different management criteria and utility functions to adapt it to different decision problems. Highlights: Sustainable fisheries must trade off different, possibly conflicting, objectives. A multi-criteria framework was developed to support decision-making in fisheries. The performances of each management scenario are summarized into an overall utility. The proposed framework is applied to a Mediterranean demersal fishery (GSA 18). The framework is flexible and can be easily adapted to different decision problems.